Managing the ‘Thyroid Diabetes’ Scenario with Homeopathy (Homoeopathy for All, 2023)
In the recent times, endocrine  disorders have seen a rise in trend,  of which Diabetes mellitus (DM)  and Thyroid disorders are the most  common ones. A patient suffering  from thyroid dysfunction for a long  duration may develop diabetes or  vice versa. Ultimately, both of these  disorders tend to co-exist in the  patients suffering from one or the  other for a prolonged duration. Such  metabolic and endocrine related  disorders tend to affect the body in  multiple ways, which may clinically  represent as body mass or weight  changes, restriction in growth pattern,  impairment in functioning of other  vital organs, psychological changes  and so on. These disorders may co exist maximum in adult males or  females, antenatal scenario, and less  commonly in adolescence. Many  physicians are able to manage both the  conditions independently. However,  when it comes to their co-existence  there are many obstacles experienced  by a practitioner. This article focuses  on the relationship between thyroid  gland disorders and diabetes mellitus  in the population and their possible  homeopathic management as per the  literature.
Keywords: psychological; mellitus; Thyroid